Association between polymorphisms of TAS2R16 and susceptibility to colorectal cancer - Barontini, Jonathan; Antinucci, Marco; Tofanelli, Sergio; Cammalleri, Maurizio; Dal Monte, Massimo; Gemignani, Federica; Vodicka, Pavel; Marangoni, Roberto; Vodickova, Ludmila; Kupcinskas, Juozas; Vymetalkova, Veronika; Forsti, Asta; et al. (BMC gastroenterology, 2017)
BACKGROUND: Genetics plays an important role in the susceptibility to sporadic colorectal cancer (CRC). In the last 10 years genome-wide association studies (GWAS) have identified over 40 independent low penetrance polymorphic variants. However, these loci only explain around 1‑4% of CRC heritability, highlighting the dire need of identifying novel risk loci. In this study, we focused our attention on the genetic variability of the TAS2R16 gene, encoding for one of the bitter taste receptors that selectively binds to salicin, a natural antipyretic that resembles aspirin. Given the importance of inflammation in CRC, we tested whether polymorphic variants in this gene could affect the risk of developing this neoplasia hypothesizing a role of TAS2R16 in modulating chronic inflammation within the gut. METHODS: We performed an association study using 6 tagging SNPs, (rs860170, rs978739, rs1357949, rs1525489, rs6466849, rs10268496) that cover all TAS2R16 genetic variability. The study was carried out on 1902 CRC cases and 1532 control individuals from four European countries. RESULTS: We did not find any statistically significant association between risk of developing CRC and selected SNPs. However, after stratification by histology (colon vs. rectum) we found that rs1525489 was associated with increased risk of rectal cancer with a (Ptrend of = 0.0071). CONCLUSIONS: Our data suggest that polymorphisms within TAS2R16 gene do not have a strong influence on colon cancer susceptibility, but a possible role in rectal cancer should be further evaluated in larger cohorts.
Keywords: Španělsko; Female; Genetic association study; Spain; chuťový receptor typu 2; ženské pohlaví; jednonukleotidový polymorfismus; Colon cancer; TAS2R16; nádory tračníku; receptory spřažené s G-proteiny; lidé; nádory rekta; Italy; Rectal Neoplasms; Polymorphism, Single Nucleotide; Rectal cancer; Itálie; Litva; Polymorphisms; genetická predispozice k nemoci; studie případů a kontrol; Taste receptors; Genetic Predisposition to Disease; Colonic Neoplasms; Colorectal cancer; genetické asociační studie; Lithuania; Male; Case-Control Studies; Aged; Czech Republic; Receptors, G-Protein-Coupled; Česká republika; Taste Receptors, Type 2; lidé středního věku; senioři; mužské pohlaví; Cancer risk; Middle Aged; Genetic Association Studies; Humans